Funun Khat And Design / Multazimah Mat Daud ... [et al.] - Mat Daud, Multazimah; Shaari, Nazira; Abdul Aziz, Fatimah; Mohd Arif, Nor Haslina; Abdurahman, Suhana
Funun Khat and Design specialized on manufacturing Islamic Art & Design. We are trying to manufacture to the highest quality standard and it will give you many years' decoration in any place. We are a company at sizeable resources, sound management and possess a good team of dedicated and disciplined staff. We are committed to providing our customer with fast delivery, quality product and excellent back-up services besides competitive prices. The management and staff of our company are professional competent with high skill and experience in working in art and design sector. We also persist ently pursue to evaluate the future demand and needs of our clients such as that our company shall always be infused with new development of product and services to meet relevant requirements of our clients. Our company is design to provide the best available prices quality and services to our client's satisfaction and requirement. We relentlessly pursue to enhance the productivity and quality heeds at our clients.